MAEL as a diagnostic marker for the early detection of esophageal squamous cell carcinoma - Mohammad Reza Abbaszadegan; Negin Taghehchian; Azadeh Aarabi; Faride Akbari; Ehsan Saburi; Meysam Moghbeli (BMC, 2021)
Abstract Background Esophageal cancer is one of the most common malignancies among Iranians and is categorized as adenocarcinoma and squamous cell carcinoma. Various environmental and genetic factors are involved in this malignancy. Despite the recent advances in therapeutic modalities there is still a noticeable mortality rate among such patients which can be related to the late diagnosis. Regarding high ratio of esophageal squamous cell carcinoma (ESCC) in Iran, therefore it is required to assess molecular biology of ESCC to introduce novel diagnostic markers. In present study we assessed the role of Maelstrom (MAEL) cancer testis gene in biology of ESCC among Iranian patients. Methods Forty-five freshly normal and tumor tissues were enrolled to evaluate the levels of MAEL mRNA expression using Real time polymerase chain reaction. Results MAEL under and over expressions were observed in 12 (26.7%) and 9 (20%) of patients, respectively. MAEL fold changes were ranged between -4.33 to -1.87 (mean SD: -2.90± 0.24) and 1.92 to 7.72 (mean SD: 3.97± 0.69) in under and over expressed cases, respectively. There was a significant association between stage and MAEL expression in which majority of MAEL over expressed tumors (8/9, 88.9%) were in stage I/II (p<0.001). There was also a significant correlation between MAEL expression and depth of invasion in which tumor with T1/2 had higher levels of MAEL expression compared with T3/4 tumors (p=0.017). Moreover, there were significant correlations between MAEL expression, tumor size (p=0.028), and grade (p=0.003) among male patients. Conclusions Our data showed that the MAEL was mainly involved in primary stages of tumor progression and it has a declining expression levels toward the advanced stages and higher depth of tumor invasions. Therefore, MAEL can be efficiently introduced as an early detection marker among Iranian ESCC patients.